How knowledgeable are people in Nepal about rabies? - Alok Dhakal; Ramjee P. Ghimire; Sujit Regmi; Krishna Kaphle (Heliyon, 2023)
Eliminating dog-mediated human rabies cases by 2030 is a collective global pledge. Rabies is a vaccine-preventable, zoonotic, and fatal viral disease tormenting human beings and animals for at least four thousand years. An average annual fatality of 59,000 people has been reported from rabies in more than 150 countries, including Nepal. Understanding people's knowledge towards rabies is paramount to preventing this disease. A cross-sectional study was conducted in three districts, namely, Siraha, Parsa, and Parasi in Nepal, from October to December 2021 to assess the level of public awareness of rabies. Information was obtained using a structured questionnaire among 308 household heads. Study findings show that some of the respondents were unfamiliar with the term ‘rabies’. They knew major carriers or sources of rabies, but the majority of them (87.3%) did not know its causative agent. They had some idea of how rabies is transmitted from animals to humans, but they lacked a clear understanding of the fate of the animals and humans once affected cases are symptomatic. Only 35.1% of respondents knew that rabies pathogens attack and multiply in the brain tissues. Rabies vaccination in pets is critical for rabies eradication, yet only 26.3% of respondents were aware of the vaccination schedule. Nearly 90% of respondents thought post-exposure prophylaxis (PEP) to be effective immediately after a suspected animal bite. The findings show that there was a significant relationship between independent variables viz. pet ownership (X2 = 20.273, p < 0.001), level of education (X2 = 39.215, p < 0.001), household income (X2 = 13.574, p < 0.001), family size (X2 = 15.053, p < 0.001), main occupation (X2 = 11.618, p = 0.020), age (X2 = 6.982, p = 0.008) with dependent variable i. e., knowledge category (good and poor knowledge). Education to invoke awareness among rural people about rabies, its transmission and prevention, including making anti-rabies vaccines freely available, should be the priority for municipalities, public health and veterinary health authorities in the study districts and throughout the country.